2011
DOI: 10.1002/jcc.21919
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory‐based electrochemical models for the oxygen reduction reaction: Comparison of modeling approaches for electric field and solvent effects

Abstract: A series of density functional theory (DFT) based electrochemical models are applied to systematically examine the effect of solvent, local electric field, and electrode potential on oxygen reduction reaction (ORR) kinetics. Specifically, the key elementary reaction steps of molecular oxygen dissociation, molecular oxygen protonation, and reduction of a hydroxyl adsorbate to water over the Pt(111) surface were considered. The local electric field has slight influence on reaction energetics at the vacuum interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 61 publications
0
54
0
Order By: Relevance
“…[23][24][25][26][27] For example, Anderson's team calculated the activation energies of the elemental steps of ORR using reaction centre models and self-consistent ab initio calculations. [30][31][32] They indicated that the first electron transfer precedes the protonation of the adsorbed O 2 molecule, occurring with the proton formally residing as an H 3 O + species connected to the adsorbed O 2 molecule by hydrogen bonding through two additional water molecules. Other researchers also obtained the same conclusion by different approaches in investigating the first electron transfer step.…”
Section: Zidong Weimentioning
confidence: 99%
“…[23][24][25][26][27] For example, Anderson's team calculated the activation energies of the elemental steps of ORR using reaction centre models and self-consistent ab initio calculations. [30][31][32] They indicated that the first electron transfer precedes the protonation of the adsorbed O 2 molecule, occurring with the proton formally residing as an H 3 O + species connected to the adsorbed O 2 molecule by hydrogen bonding through two additional water molecules. Other researchers also obtained the same conclusion by different approaches in investigating the first electron transfer step.…”
Section: Zidong Weimentioning
confidence: 99%
“…Moreover the influences of the electrolyte has been recently approximated 34-42 by continuum models 40 or an explicit treatment of a small number of water molecules 34,36,39,41,42 . The electric field has been described 11,12,[43][44][45][46][47][48] by thermodynamic approaches 11,12,43,45,46,[48][49][50][51][52] , first-principles based multiscale models 14,15 or self-consistently minimized DFT schemes 44,47 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Finally, hydrogen bonds between adsorbed dimers have also been evaluated on Pt(111): the stabilization depends nonlinearly on the number of water adsorbates (from 0.06 to 0.2 eV). [ 23,28 ] Implicit continuum models, [ 33,34 ] bilayer-based static or dynamic explicit solvation models, [35][36][37][38][39][40][41] and confi ned thinliquid systems [42][43][44] have been proposed to evaluate the chemical properties of water/Pt(111) interfaces. All these interesting studies have not focused on the effects of liquid water on the adsorption strength at the interface.…”
Section: Introductionmentioning
confidence: 99%